2015
DOI: 10.1093/cercor/bhv094
|View full text |Cite
|
Sign up to set email alerts
|

Task-Specific Facilitation of Cognition by Anodal Transcranial Direct Current Stimulation of the Prefrontal Cortex

Abstract: We previously speculated that depression of cerebellar excitability using cathodal transcranial direct current stimulation (tDCS) might release extra cognitive resources via the disinhibition of activity in prefrontal cortex. The objective of the present study was to investigate whether anodal tDCS over the prefrontal cortex could similarly improve performance when cognitive demands are high. Sixty-three right-handed participants in 3 separate groups performed the Paced Auditory Serial Addition Task (PASAT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 53 publications
2
60
4
Order By: Relevance
“…We suggest that increasing activity of the lDLPFC by anodal tDCS leads to enhanced cognitive control over relevant stimuli (naming the color but not the word) by maintaining them in WM. The observation that performance of the GoNo/Go and Stroop tasks are differently altered by DLPFC activation implicates that the activation of these regions is task-specific (Pope, Brenton, & Miall, 2015). Moreover, it also suggests that the relevance of the interhemispheric balance for task performance is also task-or domain-specific, since an impact of suggested alterations of interhemispheric balance on performance was only observed for response inhibition, but not other EF domains.…”
Section: Discussionmentioning
confidence: 93%
“…We suggest that increasing activity of the lDLPFC by anodal tDCS leads to enhanced cognitive control over relevant stimuli (naming the color but not the word) by maintaining them in WM. The observation that performance of the GoNo/Go and Stroop tasks are differently altered by DLPFC activation implicates that the activation of these regions is task-specific (Pope, Brenton, & Miall, 2015). Moreover, it also suggests that the relevance of the interhemispheric balance for task performance is also task-or domain-specific, since an impact of suggested alterations of interhemispheric balance on performance was only observed for response inhibition, but not other EF domains.…”
Section: Discussionmentioning
confidence: 93%
“…Pope et al (2015) showed that tDCS over prefrontal cortex may have differential effects depending on the complexity of the task. In their study, after anodal tDCS they observed an enhancement of a cognitive subtraction task but not of a less challenging addition task (Pope et al 2015). It is possible that the SDMT is not sensitive or challenging enough to be affected by fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antidepressant properties, some research has suggested that tDCS may have beneficial neurocognitive effects in both healthy participants and patients with neuropsychiatric disorders, including unipolar and bipolar depression (Martin et al, 2015; Minchino et al, 2015; Moreno et al, 2015; Oliveira et al, 2013; Pope, Brenton, & Miall, 2015). Specific effects include improvement in neurocognitive functions such as attention, processing speed, learning and memory, and working memory.…”
Section: Introductionmentioning
confidence: 99%